Impacto de la violencia intrafamiliar en el autoestima de los niños de cuarto año de educación general básica de la escuela Dr. Luis Felipe Chàvez de la parroquia Belisario Quevedo, cantón Latacunga - Chicaiza Marín, Wilmer Alexis (2016)
Actually the domestic violence affects to the children in many areas of education; the present investigation has an objective that is the impact of the domestic violence in the self-esteem to the kids, since teachers must be capacited to control the violence at homes in the students with the goal that it doesn´t affect the academic yield of the students, to guide with a high self-esteem make them with a critical behavior and reflective in some aspects to resolve problems. For that reason it´s necessary to create and implement a methodological guide of workshops for parents as the same as according to the educative exigencies in the actually. Based on analysis and studies to the parents information so teachers and students are immersed in the education by means of the application to the survey and interview. To explain, to show important themes like: parents school, how to make good parents, the relationship between the teacher to the student and how to maintain the good conditions each other….